2020
DOI: 10.1016/j.artd.2020.07.033
|View full text |Cite|
|
Sign up to set email alerts
|

A Case of Titanium Pseudotumor and Systemic Toxicity After Total Hip Arthroplasty Polyethylene Failure

Abstract: We describe the case of a 57-year-old female who underwent bilateral ceramic-on-polyethylene total hip arthroplasties performed in 2015. She presented to us in 2018 with headaches, fatigue, and right hip pain 5 months after an atraumatic right polyethylene liner failure for which she did not seek treatment. She was found to have imaging consistent with an adverse local tissue reaction and massive pseudotumor formation. During revision surgery, fracture of the acetabular liner was noted, with ceramic head wear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…To induce osteolysis, Ti particles were implanted into mouse calvaria. This model allowed the measurement of bone resorption in vivo owing to Ti particle-induced activated osteoclasts, which are typically generated in the Ti-implanted sites of patients ( 34 ). Despite excluding the load-bearing effect that can induce additional osteoclast-mediated bone resorption, Ti-particle-induced inflammation and osteoclast differentiation were detected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To induce osteolysis, Ti particles were implanted into mouse calvaria. This model allowed the measurement of bone resorption in vivo owing to Ti particle-induced activated osteoclasts, which are typically generated in the Ti-implanted sites of patients ( 34 ). Despite excluding the load-bearing effect that can induce additional osteoclast-mediated bone resorption, Ti-particle-induced inflammation and osteoclast differentiation were detected.…”
Section: Resultsmentioning
confidence: 99%
“…However, weight or load bearing can gradually generate wear particles of various sizes from the implants over time. These nano- to micro-sized wear particles induce inflammation, oxidative stress and periprosthetic osteolysis, and may subsequently result in implant failure ( 34 36 ). To the best of our knowledge, the present study is the first to demonstrate that britanin exerts antiosteoclastic activity, indicating its therapeutic potential against wear particle-induced osteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible complication of arthroplasty, which has mainly been described after total hip arthroplasty (THA), 6 is the formation of a pseudotumor. A pseudotumor is an aseptic, nonmalignant mass 7 that is seen in metal-on-metal (MoM), metal-on-polyethylene (MoP), and metal-on-ceramic (MoC) implants. 8 Although pseudotumors are a frequently described complication after THA, it has, to our knowledge, only been described once after TWA.…”
mentioning
confidence: 99%
“…Plasma titanium level was 460 µg/L and plasma cobalt, chromium and aluminum levels were in the normal ranges. The case report did not describe any further investigations and the clinical course after surgical revision is unknown J o u r n a l P r e -p r o o f [36]. In the second case, a 64-year-old male patient with arterial hypertension was also found to have renal failure (serum creatinine: 2.26 µg/dL) at the time of discovery of failure of his hip arthroplasty.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 95%
“…Urine titanium level was normal (Table 1), which is not surprising, as renal excretion of titanium is known to be very slow [12,15], and several publications have shown that metal concentrations may be elevated in blood (whole blood, plasma or serum) [18,19,22,27,29], but not in urine [18,22] in patients with titanium alloy prostheses. Patients with loosened titanium components generally exhibit elevated blood titanium levels (up to 620 µg/L for serum or plasma) [2,10,34,36]. Blood titanium level can be considered to be a biomarker of orthopedic implant wear.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%